COMPARATIVE ANALYSIS OF PAREMIOLOGICAL UNITS ON THE THEME “WEDDING” IN THE UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2025)
This article presents a comparative study of paremiological units (proverbs and sayings) on the theme of “wedding” in Uzbek and English. The study analyzes the structural and semantic features of proverbs and sayings reflecting the concept of “wedding” and the findings highlight isomorphic (similar) and allomorphic (different) features.